HUBUNGAN DISIPLIN BELAJAR DENGAN HASIL BELAJAR PKn di SEKOLAH DASAR - Oktaviany, Zarni; Zuardi, Zuardi; Abidin, Zainal (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
AbstractThis research approach to know correlation between the discipline of learning and students learning outcomes in learning civic education. Type of this research is quantitative correlational. Sample of this research is students of Primary school 10 ATTS and 12 Bukit Cangang, both of the two schools fulfill the research requirements of 50 students, which means that 19% of the population were selected based on cluster random sampling technique. The calculation of research data showed pearson correlation values rcalculation 0,978  > rtable 0,284.  Significance level α = 0,05. The coefficient of determination is 0,956 or 95,6% in a very strong category. This means that the learning discipline is very closely related to students learning outcomes. Keywords: discipline of  learning,  civic education learning outcome